Transformation Of The Visual Motifs Of The Kamasan Puppets Into Figurative Characters - Devi, Putu Durga Laksmi; Utami, Ni Made Purnami; Sujana, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
This thesis contains a description of the creation of a work of painting with the theme "Transformation of Visual Motifs of Wayang Kamasan into Figurative Figures" which was inspired by the motifs of Wayang Kamasan paintings on the ceiling of Kertagosa Hall, Klungkung, Bali. The Wayang Kamasan characters already have rules or 'standards' that must be preserved, but for the author when observing the decorative motifs of the Wayang Kamasan characters from the coils to the clothes, it provokes subconscious associations which actually give rise to their own figurative characters. Then deformation and stylization of motifs will be carried out to create imaginary results from icons in order to create figurative character symbols in the style of the author. For this reason, research was carried out to obtain assessment data using four theories, namely Carl Gustav Jung's archetype theory, Janques Lacan's imaginary theory, Susanne K. Langer's symbolic theory and A.A.M.'s aesthetic theory. Djelantik to explain this thesis. The author also uses two creation methods as inspiration originating from the 6 (six) stages of Mr. I Made Wiradana's work and the Mobile Art Labortory (MAL) which provides a Blueprint process for ideas and the formation of Mr. I Wayan Sujana's work 'Suklu'. The author obtained the results of the creation of the deformation and stylization of Wayang Kamasan motifs into figurative figures in the form of paintings using various techniques and media by considering the elements and principles of fine art. From the theme above, there are 6 (six) works that have been realized with narratives originating from the connection between the author's experiences and the side of humanism.